Activity of the Aurora Kinase inhibitor VX-680 against Bcr/Abl positive acute lymphoblastic leukemias - Fei, Fei (2010)
The emergence of resistance to tyrosine kinase inhibitors due to point mutations in Bcr/Abl is a challenging problem for Philadelphia-chromosome positive (Ph-positive) acute lymphoblastic leukemia (ALL) patients, especially for those with the T315I mutation, against which neither nilotinib or dasatinib shows significant activity. VX-680 is a pan-Aurora kinase inhibitor active against all Bcr/Abl proteins but has not been extensively examined in preclinical models of Ph-positive ALL. Here, we have tested VX-680 for treatment of Bcr/Abl positive ALL when leukemic cells are protected by the presence of stroma. Under these conditions, VX-680 showed significant effects on primary human Ph-positive ALL cells both with and without the T315I mutation, including ablation of tyrosine phosphorylation downstream of Bcr/Abl, decreased viability and induction of apoptosis. However, drug treatment of human Ph-positive ALL cells for 3 days followed by drug removal allowed the outgrowth of abnormal cells 21 days later, and upon culture of mouse Bcr/Abl ALL cells on stroma with lower concentrations of VX-680, drug-resistant cells emerged. Combined treatment of human ALL cells lacking the T315I mutation with both VX-680 and dasatinib caused significantly more cytotoxicity than each drug alone. We suggest that use of VX-680 together with a second effective drug as first-line treatment for Ph-positive ALL is likely to be safer and more useful than second-line treatment with VX-680 as monotherapy for drug-resistant T315I Ph-positive ALL.